Impact of Fatty Pancreas on Postoperative Pancreatic Fistulae: A Meta-Analysis - Zhou, Lu; Xiao, Wei-ming; Li, Cheng-peng; Gao, Yi-wen; Gong, Wei-juan; Lu, Guo-tao (Frontiers in Oncology, 2021)
Abstract Background: Soft pancreas is widely recognized as the most important risk factor for the development of postoperative pancreatic fistula, although fatty pancreas has not been formally defined as a cause of pancreatic fistula, existing research has shown that fatty pancreas(FP) increases the incidence of postoperative pancreatic fistula (POPF) by increasing pancreatic tenderness, therefore it may be a potential risk factor for postoperative pancreatic fistula. This study aimed to discern whether FP was associated with POPF. Method: Two reviewers independently performed literature searches from five electronic databases. According to the established inclusion criteria, we extracted the data we needed from the studies that met the criteria for further analysis. We pooled the odds ratios (OR) from individual studies using a random-effects model to investigate associations between POPF and the prognosis of FP. Result: A total of 11 studies (encompassing 2484 individuals) were included. The pooled prevalence of POPF was 18% (95% CI: 12-24%). Body mass index (BMI) was associated with a significantly increased risk of POPF (OR=3.55; 95% CI: 1.83,6.86; P=0.0002; I²=0). FP was conspicuously associated with the occurrence of POPF (OR=3.75; 95% CI: 1.64,8.58; P=0.002; I²=78). Conclusion: FP is closely associated with the development of POPF, and the early identification of these high-risk patients is helpful to reduce the incidence of POPF.